Penerapan Model Pembelajaran Interaktif untuk Meningkatkan Hasil Belajar Dasar Teknik Pemesinan pada Siswa Kelas XI Tpm Smk TPI Gedangan Sidoarjo - Ashari Ashari (Syntax Literate, 2023)
In every learning teacher always uses approaches, strategies, methods and learning models to make it easier for students to understand the material they teach. This study aims to describe the application of interactive learning models to improve machining engineering learning outcomes in grade XI TPM SMK TPI Gedangan Sidoarjo students. The method used in this study is the Classroom Action Research (PTK) method. This research consists of two cycles, cycle I is carried out in accordance with the learning plan and cycle II is guided by the results of cycle I reflection. The research was carried out at SMK TPI Gedangan Sidoarjo, the subject of the study was 35 grade XI TPM students. The data collection method uses observation sheets, performance sheets/short description questions, and questionnaire sheets for student responses to interactive learning models. Data analysis uses qualitative descriptive analysis techniques. The results showed that interactive learning models can improve student learning outcomes. Improved results can be seen from the increase in student learning completeness achievement in each cycle. The achievement of student learning completeness in cycle 1 41.17% (15 students complete). After being subjected to action in cycle 2 with an interactive learning model, the achievement of student completeness increased to 85.29% or 29 students had met the KKM. 6 students who have not KKM are almost close to the score of 7.5 (KKM) which is with the lowest score of 7.00 Student learning activities also increase, because active students can awkwardly interact with their friends.